2015
DOI: 10.1101/lm.038166.115
|View full text |Cite
|
Sign up to set email alerts
|

Phase matters: responding to and learning about peripheral stimuli depends on hippocampal θ phase at stimulus onset

Abstract: Hippocampal u (3 -12 Hz) oscillations are implicated in learning and memory, but their functional role remains unclear. We studied the effect of the phase of local u oscillation on hippocampal responses to a neutral conditioned stimulus (CS) and subsequent learning of classical trace eyeblink conditioning in adult rabbits. High-amplitude, regular hippocampal u-band responses (that predict good learning) were elicited by the CS when it was timed to commence at the fissure u trough (Trough group). Regardless, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
6
18
1
Order By: Relevance
“…In fact, almost all (90%) of the animals in the diastole group reached a limit of 80% CRs per session, whereas only one-half the animals in the systole group and less than one-third of those in the random group reached this limit during the 14 sessions of trace eyeblink conditioning. The animals in the diastole group also learned exceptionally well compared with previous results from our laboratory using the same paradigm for trace eyeblink conditioning (Nokia and Wikgren 2014;Nokia et al 2015;Waselius et al 2018).…”
Section: Experiments 2: Rabbit Eyeblink Conditioning and Hippocampal Fsupporting
confidence: 58%
See 1 more Smart Citation
“…In fact, almost all (90%) of the animals in the diastole group reached a limit of 80% CRs per session, whereas only one-half the animals in the systole group and less than one-third of those in the random group reached this limit during the 14 sessions of trace eyeblink conditioning. The animals in the diastole group also learned exceptionally well compared with previous results from our laboratory using the same paradigm for trace eyeblink conditioning (Nokia and Wikgren 2014;Nokia et al 2015;Waselius et al 2018).…”
Section: Experiments 2: Rabbit Eyeblink Conditioning and Hippocampal Fsupporting
confidence: 58%
“…The critical role of the hippocampal theta activity in declarative learning is supported by a multitude of experimental findings (Berry and Seager 2001;Berry and Thompson 1978;Griffin et al 2004;Wikgren 2010, 2014; for conflicting findings, see Múnera et al 2001). Overall, temporally robust hippocampal thetaband responses to the conditioned stimulus predict good learning (Nokia et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…; Nokia et al . ). Further, according to Buzsaki's theory (Buzsáki, ), during a rest period following the initial learning event, CA3 neurons potentiated most recently initiate ripples, that is, induce firing of the larger ensemble of previously activated CA3 neurons and their target CA1 pyramidal cells.…”
Section: Discussionmentioning
confidence: 97%
“…According to Buzsáki's two-stage theory (Buzsáki, 1989), during epochs of theta, granule cells in the dentate gyrus encode incoming information about external events arriving from the entorhinal cortex into weak representations in the CA3. Interestingly, the phase of theta seems to modulate hippocampal responses to external stimuli and learning about those stimuli (Hasselmo et al 2002;Nokia et al 2015). Further, according to Buzsaki's theory (Buzsáki, 1989), during a rest period following the initial learning event, CA3 neurons potentiated most recently initiate ripples, that is, induce firing of the larger ensemble of previously activated CA3 neurons and their target CA1 pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Berry et al reported that presenting trials when theta power is high results in faster learning of trace (or delay) EBC as compared with presenting trials when theta is not present (Cicchese, Darling, & Berry, ; Seager, Johnson, Chabot, Asaka, & Berry, ). Failures to replicate this effect may be due to presentation of the conditioning stimuli at a sub‐optimal phase of the theta cycle (Nokia, Waselius, Mikkonen, Wikgren, & Penttonen, ), hence an analysis of theta phase and phase resetting is important. Regardless, stimulus‐specific theta modulations in CA1 remain strong throughout acquisition and consolidated performance of trace eyeblink conditioning (Hattori, Chen, et al, ).…”
Section: Introductionmentioning
confidence: 99%